2022
DOI: 10.3390/atmos13122120
|View full text |Cite
|
Sign up to set email alerts
|

High Indoor Radon Case Study: Influence of Meteorological Parameters and Indication of Radon Prone Area

Abstract: Indoor radon and meteorological parameters (temperature, humidity, pressure, precipitation, indoor dew point, wind direction, wind speed and heat index) were simultaneously monitored in an old residential house in a radon suspected area. Measurements were performed during the period from winter to summer (13 February 2021–15 August 2021). Indoor radon concentrations were measured with detectors, Airthings Corentium Home (alpha spectrometry method), and meteorological parameters were continuously monitored by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Our finding that higher barometric pressure is associated with lower indoor radon is similar to those of three studies [ 43 45 ], in which indoor radon values were negatively correlated with outdoor barometric pressure. Chen et al [ 45 ] developed a field-validated advective-diffusive soil radon transport model to evaluate the effects of cyclic barometric pressure fluctuations on soil radon concentrations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that higher barometric pressure is associated with lower indoor radon is similar to those of three studies [ 43 45 ], in which indoor radon values were negatively correlated with outdoor barometric pressure. Chen et al [ 45 ] developed a field-validated advective-diffusive soil radon transport model to evaluate the effects of cyclic barometric pressure fluctuations on soil radon concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has shown a complicated relationship between indoor radon levels and soil moisture or precipitation. Some studies have reported an association between precipitation or soil moisture and increased indoor radon levels [ 56 58 ], whereas others have reported minimal or no correlation between rainfall and indoor radon values [ 43 , 46 , 59 ]. In a study of soil radon levels, Sundal et al [ 60 ] found associations between soil radon and both temperature and barometric pressure, but not precipitation or soil moisture.…”
Section: Discussionmentioning
confidence: 99%
“…Strong daily fluctuations were recorded throughout the entire study period and were clearly linked to the opening and closing of the windows, respectively in the morning and in the afternoons [21][22][23][24][25], demonstrating that natural ventilation effectively and rapidly reduced radon levels. The heating system in the cold season, generally turned on in the afternoon and evening hours, further enhanced winter temperature and pressure gradients between the building and the outside, driving soil gas into the building and increasing radon highest daily values.…”
Section: Discussionmentioning
confidence: 99%
“…In the structure of mortality, lung cancer takes first place at 16.3%, stomach cancer takes second place at 12%, and colon cancer takes third place at 10.6%. According to the results of the work for 2022, the Kostanay, Akmola, Aktobe, and Mangystau regions were classified as unfavorable regions for oncological morbidity, where three out of five indicators are higher than international ones [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%